Digital switchover in Central and Eastern Europe: Premature or badly needed? - Jakubowicz, Karol (Javnost-The Public, 2007)
Preparation for the digital switchover in Central and Eastern Europe adds to the complexity of post-Communist transformation in broadcasting. The following problems are apparent: (1) lack of sufficient understanding of the issues involved in the digital switch-over, especially as regards the broadcasting, programming and market issues involved; (2) turf wars between broadcasting and telecommunications regulatory authorities; (3) the impact of politics on the process of preparation and execution of digital switchover strategies; and (4) in some cases, launching the process prematurely, for inappropriate reasons. Depending on one’s point of view, this is either a “premature” digital switchover in countries not yet ready for it, or a case of countries needing a wake-up call to face technological and market realities that they are not responding properly to. Poland is in the process of changing its switchover strategy. The process is to start in 2010 with the roll-out of one digital multiplex, covering the whole country, and carrying the existing analogue terrestrial television channels. Plans for further moves are hazy. Meanwhile, many market players are launching alternative projects to take advantage of digital technology, e.g. by means of satellite technology.